ANALISIS NILAI TAMBAH DAN EFISIENSI USAHA PENGOLAHAN JERUK SIAM PONTIANAK (Citrus nobilis var. microcarpa) GABUNGAN KELOMPOK TANI SUMBER ANUGERAH DESA SEGEDONG KECAMATAN TEBAS KABUPATEN SAMBAS - Wilujeng, Wilis Widi; Yurisinthae, Erlinda; Sasli, Iwan (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2013)
Objectives of this research was to analyzed the added value and business efficiency of processing of Siam Pontianak citrus in farmer group Sumber Anugerah. This research was conducted in Tebas sub-distric because this area was the center of citrus producer. Farmer group of Sumber Anugerah was choosen because the first place of citrus processing in to juice was occur here. Parameters used consist : costs of main ingredient, costs of supporting material, depreciaton costs and labors costs. There was two analytical techniques used : added value analysis and efficiency with Cobb-Douglas test. Results of the research was : 1) Bussines of citrus Processing that used main and supporting ingredients, depreciation cost and labors have no added value as much as Rp 675. 2) The use of main and supporting ingredients, costs of labours in this bussines was not efficient yet, with coefficient of efficiency was -50,09. Further more, to get added values needs to increase selling price of the juice. Efficiency will fulfill if the capacity of each process increase and the continuity of process maintain. Keywords : added value, citrus, efficiency, juice, processing